Effects of desilication pretreatment on rice husk/high‐density polyethylene bio‐composites. Issue 3 (18th December 2020) - Yang, Yingni; Pang, Yao; Zhang, Weiye; Xia, Rongqi; Li, Yanchen; Liu, Yi; Guo, Hongwu
Abstract: Rice husk (RH) is a productive agricultural residue; however, its materialization is limited by its inherent properties. The comprehensive utilization of RH can be improved via pretreatment using physical and chemical methods. In this study, we explored the effect of pretreatment (shearing, grinding, and alkaline) on the properties of RH, as well as the bio‐composites developed using RH and high‐density polyethylene (HDPE). Further, the surface morphology, chemical structure, water absorption, thermal stability, and dynamic viscoelasticity of the pretreated RH and RH/HDPE composites were investigated. The results denoted that the surface roughness of RH increased and that the silicon content partially decreased. The water absorption of the RH/HDPE composites pretreated by physical pretreatment was <2%. The occurrence of dynamic viscoelasticity indicated that the RH/HDPE composites pretreated by alkaline exhibited improved rigidity and mechanical properties. In the composites prepared using the RH pretreated by grinding, a strong bonding could be observed between the interfaces of HDPE and RH. Hence, the efficiency of RH utilization can be improved by pretreatment, and the prepared bio‐composites can increase the value of RH.